Análisis de las comunidades de microhongos de la hojarasca de Scutia buxifolia (Rhamnaceae) en el este de la provincia de Buenos Aires, Argentina - Allegrucci, Natalia (2005)
Decomposer saprotrophic mycobiota of leaf litter from woods of Scutia buxifolia (Coronillo) was analyzed in both disturbed and non disturbed areas, evaluating their seasonal variations. The relative frecuency of each species was calculated, and this information was used to establish the Diversity Index (Shannon-Weaver), H; species richness, S; and evenness, E. From the analysis of the fungal community of Coronillo in both areas, we found the fungal community has not changed regarding disturbance, although its effects is reflected in the species richness and relative frecuency of the species. A principal component analysis showed seasonal tendencies: some species were found to be abundant in summer-autumn whereas others had higher abundance in winter-spring.